Sensory Phenomenon Assessment Scale: a new tool for assessment of tic-associated sensations - Wang, Xianbin; Li, Yanlin; Yu, Liping; Xu, Hui; Zhang, Anyi; Zhang, Wenyan; Jiang, Zhongliang; Cui, Yonghua; Li, Ying (Frontiers in Psychiatry, 2024)
Background Sensory symptoms linked to tic disorder (TD) are challenging to quantify via self- or parent-reported measures. The current study aimed to develop a novel observer-rated semi-structured interview, namely, the Sensory Phenomenon Assessment Scale (SPAS), to aid clinical evaluation on symptoms of TD among children. Methods To test its psychometric properties, tic, premonitory urge (PU), and obsessive–compulsive symptoms (OCS) were also assessed in 223 children via the Yale Global Tic Severity Scale (YGTSS), the Premonitory Urge for Tic Scale (PUTS), and the Children’s Yale–Brown Obsessive–Compulsive Scale (CY-BOCS). Factor analysis and internal consistency test were carried out using data from TD-diagnosed individuals. Results Good internal consistency and test–retest reliability were observed. Criterion validity was established by significant correlations between the PUTS, the YGTSS, the CY-BOCS, and scores of the SPAS. Factor analyses supported a single-factor model of the SPAS, in which the five items each showed a factor loading above 0.6. Conclusion This study demonstrated that the SPAS is reliable and valid and, thus, can serve as a good and concise measure of clinical symptoms among children and adolescents with TD.